Which variables are associated with recruitment failure? A nationwide review on obstetrical and gynaecological multicentre RCTs (2003–2023) - Ben W Mol; Madelon van Wely; L Ramos; J J Duvekot; J B Derks; Fulco van der Veen; Ruben Duijnhoven; H J van Beekhuizen; M J E Mourits; J A M van der Post; E Pajkrt; M A Oudijk; et al. (BMJ Open)
Objective We aim to assess which variables are associated with recruitment failure of obstetrical and gynaecological randomised controlled trials (RCTs), leading to an extension of the study period.Design Nationwide study.Setting A cohort of RCTs supported by the trial centre of the Dutch Consortium of Obstetrics and Gynaecology.Population We included 83 RCTs that recruited patients between 1 March 2003 and 1 December 2023.Main outcome measures Main outcome was recruitment target not achieved within 6 months after the preplanned recruitment period. Secondary outcomes were recruitment target not achieved within an extension period of at least 12 months and premature termination of the trial. In all RCTs, we collected information on variables with a potential effect on recruitment failure, recorded at five levels; patient, doctor, participating centre, study organisation and study design.Results In total, 46 of 83 RCTs (55%) did not achieve their targeted recruitment within the preplanned study period with a maximal extension period of 6 months. The most relevant variables for recruitment failure in multivariable risk prediction modelling were presence of a no-treatment arm (where treatment is standard clinical practice), a compensation fee of less than €200 per included patient, funding of less than €350 000, while a preceding pilot study lowered this risk.Conclusions We identified that the presence of a no-treatment arm, low funding and a low compensation fee per included patient were the most relevant risk factors for recruitment failure within the preplanned period, while a preceding pilot study lowered this risk. Awareness of these variables is important when designing future studies.